Efficiency of forest chip transportation from Russian Karelia to Finland - Goltsev, Vadim; Trishkin, Maxim; Tolonen, Timo (Finnish Forest Research Institute, 2011)
Layout: Anne Siika Nowadays the development of bioenergy in Russian Karelia is hindered by various factors. However, the development of modern cut-to-length harvesting techniques, available wood resources and Russian customs policy have created opportunities to export forest chips from Russian Karelia to Finland. An important factor for the export is the total supply cost of Russian forest chips to Finland. This depends to a large degree on the costs of transportation of the forest chips. In this study the efficiency and costs of cross-border transportation of forest chips were analysed and compared with the efficiency and costs of transportation of forest chips of Finnish origin.Data collected from various companies involved in forest chip production and their supply from Russia to Finland were used to calculate the costs of cross-border transportation of forest chips and to estimate the average productivity of chip trucks delivering from Russia to Finland. These outputs were compared with the transportation costs and productivity of chip trucks within Finland and Russia.Truck drivers involved in cross-border transportation of forest chips were also interviewed to determine factors affecting the efficiency of forest chips transportation.In addition, the quality characteristics of the Russian forest chips being supplied to Finland were analysed.Analysis of transportation costs showed that the highest costs for the 80 km reference distance are those within Finland 4.7 /loose m3, the costs on the cross-border route studied, from Lendery (Republic of Karelia) to Lieksa (Finland) through the Inari border crossing point, are 3.4 /loose m3 and transportation costs within Russia are 3.5 /loose m3.Transportation costs as a proportion of the total supply costs were highest for forest chips imported from Russia at 26%, whereas in Finland and Russia they were 23% and 19% respectively.According to the results of the interviews, bad road conditions and idle time on the border were recognized as the main factors decreasing ...